E-government impacts on effectiveness: a survey study of an e-official-document system. (13th March 2006) - Sun, Szu-Yuan; Ju, Teresa L.; Chen, Pi-Yu
Government promulgates directives and disseminates information through official documents. An internet-based official document processing system will not only expedite the document processing flow, which in turn improves administration efficiency, but also result in big savings on paper, envelop, postage, etc. Furthermore, the transport of documents will no longer be affected by the weather or distance, which in turn affords promptness and reliability. This study constructed a research model to measure the effectiveness of an e-official-document system deployed in Pingdong County in Taiwan, in terms of its impact on user satisfaction, individual performance and the performance of subordinate agencies.